Monitoring of Heavy Metal Polution the Lead (Pb) with Bio Indicator Baung Fish (Hemibagrus nemurus) at the Musi River of South Sumatra - Rizqi Safitri; Jhon Riswanda; Fahmy Armanda (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Safitri R, Riswanda J, Armanda F. 2020. Monitoring ofÂ heavy metal polution the lead (Pb) with bio indicator baung fish (Hemibagrus nemurus) at the Musi River of South Sumatra. Jurnal Lahan Suboptimal : Journal of Suboptimal Lands 9(2): 127-138.The high activity of the community in the musi river waters could affect the quality of river water, and can even caused water pollution and aquatic biota including fish baung (Hemibagrus nemurus) by lead heavy metals (Pb). This study aimed to determine the lead (Pb) heavy metal content of baung fish (H. nemurus) catches of fishermen in the musi river waters of palembang city. This research was conducted in May-June 2019. The method used is quantitative descriptive. The sample of this research is the meat, skin, liver, kidney and gill of baung fish (H. nemurus) which are tested for lead (Pb) heavy metal content using aas (atomic absorption spectrophotometry). The results of this study indicated that the concentration of heavy metal the lead (Pb) in fish baung (H. nemurus) in the waters of the musi river on the average meat of 0.046 mg/kg, on the skin of 0.058 mg/kg, in the liver of 0.1516 mg/kg, in the kidney at 0.2513 mg/kg, and in the gills at 0.2216 mg/kg. The Pb concentration on the meat, skin and liver samples were still below the established quality standards so that they were still suitable for consumption while the kidney and fish gill samples are above the quality standards that have been set based on the regulations of the Regulations Drug and Food Control Agency (DFCA) number 5 of 2018 which is equal to 0.20 mg/kg.